2023
DOI: 10.21511/bbs.18(4).2023.25
|View full text |Cite
|
Sign up to set email alerts
|

Central bank independence as a prerequisite for ensuring price stability: Modeling the role of the national pattern

Atik Kerimov,
Azer Babayev,
Viktoria Dudchenko
et al.

Abstract: Ensuring price stability is a dominant function of the central bank. Empirical studies on various statistical samples give conflicting results regarding the influence of central bank independence on the inflation rate. The study offers a methodology for assessing the role of the formation of a national pattern of central bank independence in ensuring price stability. Calculations were made for 53 countries of the world using a combination of cluster analysis tools and panel regression modeling. The cluster ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Political power attempts to achieve short-term economic growth through an expansionist monetary policy that created inflation to sway public opinion and win elections (Beju, 2008;Ouyang et al, 2022). Many empirical studies have found that average inflation is negatively related to CBI measures (Cukierman et al, 1992;Eijffinger & de Haan, 1996;Walsh, 2003;Vasylieva et al, 2022;Khokhych et al, 2023;Kerimov et al, 2023aKerimov et al, , 2023b; studies have shown that countries with higher levels of CBI tend to have lower inflation rates and are more successful in controlling inflation. The relationship between CBI and monetary stability has been a subject of extensive empirical analysis in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Political power attempts to achieve short-term economic growth through an expansionist monetary policy that created inflation to sway public opinion and win elections (Beju, 2008;Ouyang et al, 2022). Many empirical studies have found that average inflation is negatively related to CBI measures (Cukierman et al, 1992;Eijffinger & de Haan, 1996;Walsh, 2003;Vasylieva et al, 2022;Khokhych et al, 2023;Kerimov et al, 2023aKerimov et al, , 2023b; studies have shown that countries with higher levels of CBI tend to have lower inflation rates and are more successful in controlling inflation. The relationship between CBI and monetary stability has been a subject of extensive empirical analysis in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%